Od „bibliotek fotograficznych” do "fototek". O epistemologicznym potencjale historyczno-artystycznych kolekcji fotografii - Caraffa, Constanza; Lipiński, Filip (Artium Quaestiones, 2022)
This text is a translation from English into Polish of a fundamental text for research into reproductions of works of art, written by Constanza Caraffa, the leading theorist of the field. It is an introductory chapter of her important volume Photo Archives and the Photographic Memory of Art History (2011), in which she elucidates the meaning of a photo-archive as a site of research into photographs of works of art as individual, material objects. Using examples and her work experience in the Photothek at the Kunsthistorische Institut in Florence, she presents the complexity and abundance of information that photographic reproductions of works of art can carry, over and above the traditional understanding of a photograph as a document transparent onto the object it represents.